Blockade of GCH1/BH4 Axis Activates Ferritinophagy to Mitigate the Resistance of Colorectal Cancer to Erastin-Induced Ferroptosis - Hu, Qian; Wei, Wanhui; Wu, Daiqian; Huang, Fengxing; Li, Mengting; Li, Wenjie; Yin, Jingwen; Peng, Yanan; Lu, Yuanyuan; Zhao, Qiu; Liu, Lan (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis, a type of cell death triggered by excessive accumulation of iron-dependent lipid peroxidation, possesses an excellent potential in cancer treatment. However, many colorectal cancer (CRC) cell lines are resistant to ferroptosis induced by erastin and RSL3, the classical ferroptotic inducers. Moreover, the underlying mechanism of resistance remains poorly elucidated. This study sought to discover the major factor contributing to ferroptosis resistance in CRC. The study findings will help design strategies for triggering ferroptosis for application in individualized tumor therapy. Here, we show that tetrahydrobiopterin (BH4) determines the sensitivity of CRC cells to ferroptosis induced by erastin. GTP cyclohydrolase-1 (GCH1) is the first rate-limiting enzyme of BH4. Genetic or pharmacological inhibition of GCH1 decreased BH4 and assisted erastin in cell death induction, lipid peroxidation enhancement, and ferrous iron accumulation. BH4 supplementation completely inhibited ferroptotic features resulting from GCH1 knockdown. Unexpectedly, GCH1 knockdown failed to enhance RSL3-induced cell death in CRC. Mechanistically, GCH1 knockdown drastically activated ferritinophagy during erastin treatment rather than RSL3 treatment. Administration of an autophagy inhibitor reversed erastin resistance in GCH1-knockdown cells. GCH1 inhibitor and erastin co-treatment in vivo synergistically inhibited tumor growth in CRC. Overall, our results identified GCH1/BH4 metabolism as a burgeoning ferroptosis defense mechanism in CRC. Inhibiting GCH1/BH4 metabolism promoted erastin-induced ferroptosis by activating ferritinophagy, suggesting that combining GCH1 inhibitors with erastin in the treatment of CRC is a novel therapeutic strategy.